Korelasi Atribut Sensori dan Emotional Sensory Mapping Produk Minuman Fermentasi Kulit Buah Nanas (Ananas comosus L.): Correlation between Sensory Attributes and Emotional Sensory Mapping in Fermented Pineapple (Ananas comosus L.) Peels Beverage - Caca Pratiwi; Iza Ayu Saufani; Latifah Rahman Nurfaziah (Amerta Nutrition, 2025)
Background: The commercial development of tepache beverages requires systematic mapping of sensory attributes, such as the Check-All-That-Apply (CATA) method, to ensure alignment with consumer perceptions. However, integration of emotional responses during sensory evaluation remains relatively underexplored. Emotional profiling offers complementary insights alongside conventional sensory acceptance data, offering a more holistic understanding of consumer responses to the product. Objectives: This study aimed to identify the sensory profile of tepache beverages using the CATA method and to determine emotional profiling through the Emotional Sensory Mapping (ESM). Methods: This study was conducted in two stages: Sample preparation and sensory testing. The materials used included three formulations of tepache beverage (A, B, C), mineral water, and crackers. The tools utilized were stationery, questionnaires, cups, and the XLSTAT 2020 software. Results: Correspondence Analysis showed that product A is closely correlated with acidity, product code B with citrate, and product code C with sparkle. Emotional profiling in Cochran’s Q test revealed significant difference at 5% level, with relaxing, energy, plain, and satisfied influencing consumer perceptions. Conclusions The correlation between the mouthfeel sensory attributes and preference for the tepache beverage samples was found in sweetness and richness, while the sensory attributes at swallow were lightness and richness. Emotional profile mapping indicates that consumers prefer relaxing emotional response observed in product C.